Age-dependent resistance to murine retrovirus-induced spongiform neurodegeneration results from central nervous system-specific restriction of virus replication. - Czub, M (1991)
The murine retrovirus CasBrE causes a noninflammatory spongiform degeneration of the central nervous system (CNS). Mice inoculated as neonates develop viremia and are susceptible to disease. However, mice inoculated at 10 days of age do not develop viremia and are totally resistant to the neurologic disease. We recently described a highly neurovirulent chimeric virus, FrCasE (J. L. Portis, S. Czub, C. F. Garon, and F. J. McAtee, J. Virol. 64:1648-1656, 1990), which contains the env gene of CasBrE. Mice inoculated at 10 days of age with this virus developed a viremia comparable to that in neonatally inoculated mice but, surprisingly, were still completely resistant to the neurodegenerative disease. A comparison of the tissue distribution of virus replication for mice inoculated at 1 or 10 days of age was determined by Southern blot analysis for the quantification of viral DNA and by infectious-center assay for the quantification of virus-producing cells. The levels of virus replication in the spleens were comparable in the two groups. In contrast, virus replication in the CNS of the resistant 10-day-old mice was markedly restricted (100- to 1,000-fold). Intracerebral inoculation did not overcome this restriction. A similar pattern of CNS-specific restriction of virus replication and resistance to disease was observed in athymic NIH Swiss nude mice inoculated at 10 days of age, suggesting that T-cell immunity was not involved. From our results, we conclude that the age-dependent resistance to disease is a consequence of the restriction of virus replication within the CNS due to the developmental state of the organ.